IMPLEMENTASI TANGGUNG JAWAB KEJAKSAAN NEGERI DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA (STUDI FIELD RISET PERPUTAKAAN) - Boby Daniel Simatupang; Edy Kristianta Tarigan (Lex Justitia, 2021)
One of the law enforcement agencies that have competence in eradicating criminal acts of corruption is the authority of the Prosecutor's Office. Therefore, a study was conducted on the implementation of the Attorney General's responsibility in handling corruption in order to find out the obstacles and efforts to eradicate corruption eradication. Therefore, this paper discusses "Implementation of Public Prosecutor's Responsibility in Eradicating Corruption in Indonesia". The research method used in this research is analytical descriptive method, which means a study that describes, examines, explains and analyzes the law both in the form of theory and practice and approaches to library research with content analysis (content analysis) from a variety of relevant references on issues that are currently. Research results explain the authority of the Prosecutor's Office as investigators, prosecution and implementation of Judges' decisions in accordance with Law No. 16 of 2004. Obstacles in the authority of the prosecutor's office in Corruption Eradication, namely (1). Structural Barriers; (2) Cultural Barriers; (3). Management Barriers; (4). Instrumental Barriers. As for the suggestion is the need to strengthen the attorney's authority in the field of wiretapping and it is hoped that related parties, especially the Government, will make / draft laws and regulations (Draft Law) on the Prosecutor's Office to sharpen the function and authority in eradicating Corruption.